Lithium Toxicity - A Chameleon to Gastrointestinal Vasculitis as an Initial Presenter of Systemic Lupus Erythematosus - Guru, Satyabrata; Behera, Anupama; Barik, Sadananda; Sahu, Ajitesh (International journal of applied and basic medical research, 2023)
Systemic lupus erythematosus (SLE) is a multisystemic autoimmune disease. Gastrointestinal manifesting as nausea, vomiting, and pain abdomen are not so uncommon in SLE flare. However, gastrointestinal intestinal vasculitis as an initial presenter of SLE is very rare. This case report narrated gastrointestinal vasculitis as an initial presentation of systemic lupus erythematous, which mimicked lithium toxicity in a patient of preexisting bipolar disorder who was on long-term lithium therapy. A 26-year-old female presented with abdominal pain and persistent vomiting for 2 months. On further workup, she was antinuclear, anti-Smith, and anti-ds-DNA antibody positive. The serum lithium level was found to be normal computed tomography angiogram of the abdomen suggestive of vasculitis. A final diagnosis of SLE with gastrointestinal vasculitis as an initial presenter was made. She was treated with high-dose corticosteroid, cyclophosphamide, and other supportive care. She improved dramatically and was discharged with an oral corticosteroid, hydroxychloroquine, and ramipril.